Pediatric esophageal stricture after chemical ingestion - Veloso, Amanda Teixeira; Fidélio, Cibelly Leite Wanderley; Prado, Ellen Caroline Silva; Oliveira, Hanne Karoline Lopes; Saraiva, Hugo Severo; Milhomem, João Victor Braga; Silva, Joyce Giovana da; Oliveira, Thaysa Renata Jorge; Silva, Vitor Fiori Paulo Kopke; Falavigna, Vinicius Fernando Pereira (Seven Editora, 2024)
Pediatric esophageal stricture following ingestion of chemical substances is a condition that arises from the accidental ingestion of caustic products by children. This ingestion can cause damage to the esophagus, leading to the formation of scars and narrowing of the organ. Diagnosis involves examinations such as endoscopy and radiographs, while treatment may include esophageal dilation and, in some cases, surgical intervention. Regular medical follow-up is essential to monitor development and ensure an effective therapeutic approach, aiming to improve the quality of life for the affected child. DOI:https://doi.org/10.56238/sevened2024.001-026